1990
DOI: 10.1007/bf00173721
|View full text |Cite
|
Sign up to set email alerts
|

Emulsifying agents from bacteria isolated during screening for cells with hydrophobic surfaces

Abstract: The culture supernatants of 126 bacterial strains isolated during screening for hydrophobic cell surfaces, were tested for the production of emulsifying agents. Forty-eight strains were found to produce effective emulsion-stabilizing substances during growth on glucose. The most effective emulsifying agents were isolated and could be divided into two chemical groups. The first group was separated from the isolated extracts by the use of thin-layer chromatography and detected as ninhydrin-negative, 4,4'-tetrame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 34 publications
2
43
0
1
Order By: Relevance
“…The isolation (Neu & Poralla, 1987) and identification (Neu & Poralla, 1988) of Rhodococcus strain No. 33 were described previously.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The isolation (Neu & Poralla, 1987) and identification (Neu & Poralla, 1988) of Rhodococcus strain No. 33 were described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Gel permeation chromatography was done using Sepharose CL 4B, with a fractionation range of 3 x 104-5 x lo6, in 0.2 M-ammonium acetate buffer. The production of antibodies against the isolated polysaccharide was described elsewhere (Neu & Poralla, 1988).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[22,23] Tests have shown that rhamnolipids suppress the spread of breast cancer cells. [24][25][26] Rhamnolipids in the right concentration are a hemolysin, meaning that they can break up red blood cells by lysis, destroying the blood cell wall. [27,28] Rhamnolipids have numerous applications in agriculture and farming, they are effective as a fungicide and bactericide for certain agricultural pests.…”
Section: Introductionmentioning
confidence: 99%